Effectiveness of Interventional Rehabilitation Program on Swallowing Ability of Patients with Cerebrovascular Accident - Salem Hadi Al-Jubouri, Ahmed; K. Abd Ali, Diaa (International Journal of Psychosocial Rehabilitation, 2020)
Cerebrovascular disorders are a comprehensive term that refers to a central nervous system dysfunction (CNS) that occurs when normal blood flow to the brain is interrupted. Stroke is the primary cerebrovascular disorders in the United States and is the third leading cause of death after heart disease and cancer. According to the common recent WHO data released in 2017, CVA deaths in Iraq amounted to 14315, or 8.13% of all deaths. After CVA, difficulty swallowing is very common, affecting from 13 to 94 percent Acute CVA patients. A Study and Control Groups Pre-Test, Post-Test1and Post Test2 Quasi Experimental Design used to study the effect of Swallowing Method on Swallowing Ability of Patients with Cerebrovascular Accident, from the period of 1st. September 2019 to the September 2020. A non-probability (purposive sample) of (50) stroke patients are included in the study. The study conducted in Babylon City. 50Patients diagnosed with cerebrovascular accident (CVA) selected through a non-probability accidental sample were included in the study. The study is conduct in Babylon City Morgan Medical City, Hilla Teaching Hospital, and Imam Sadiq Hospital. The data are collected by using questionnaire developed by the researchers to determine the effect of the Swallowing Method on Patients Swallowing Ability. Questionnaire which consists of three parts (1) Patients’ Demographic data. (2) Patients’ clinical data. (3) Swallowing ability scale (Gugging Swallowing Screen). validity of the study instrument achieved through a panel of expert. The data described statistically and analyzed through use of the descriptive and inferential statistical analysis procedures. The findings of the present study indicate that there is an improvement in the Post Test2 group Swallowing Ability compared with the Pre Test and Post Test1 group patients’. Result the study sample indicates that there is a relationship between the effectiveness of the program and the patient age, hemiplegia, hypertension, and ataxia, age 60 and over need a longer period to return to the normal condition compared to younger ages that need a shorter period, this study shows there is a significant relationship between the interventional program and age. In addition, this study shows there is a significant association between the interventional program and problems and hypertension and the highly significant association between the interventional program and problems or complications ataxia. Furthermore, the study sample indicates significant differences in the patients’ swallowing ability (post-test 2) according to the presence of hemiplegia and ataxia. While there is a non-significant difference according to hypertension. But according to the statistical mean, the study findings indicate that the swallowing ability decreased as the patients suffer from these problems. The study concluded that the Swallowing method is an effective Swallowing Ability rehabilitation technique in improving the stroke patients’ Swallowing Ability. The study recommends to an intensive comprehensive wide population-based (national level) studies could be conducted to determine the effectiveness of the nursing rehabilitation methods in improve the patients’ health status and reduce the complications especially for patients with Cerebrovascular accident.